LB-005 Unruptured arteriovenous malformation intervention rate is inversely correlated with ruptured AVM discharge incidence. (6th August 2020) - McCarthy, D; Luther, E; Gross, B; Starke, R
Abstract : Introduction: The 2013 ARUBA trial concluded that medical management alone is superior to medical management with interventional therapy for patients with unruptured brain arteriovenous malformations. Objective: To analyze AVM treatment and epidemiologic response to the ARUBA trial. Methods: National Inpatient Sample was reviewed from 2003 to 2017, ruptured and unruptured AVMs were identified (rAVM, uAVM). Periods before and after ARUBA defined as 2010–2013 and 2014–2017. Multivariable logistic regression identified correlates to intervention likelihood. Yearly intervention rate (YIR, #interventions/#AVM discharges) and yearly rAVM incidence (YRR, #rAVM/#AVM discharges) were calculated. Segmented regression (SR) identified significant change-points and fitted segmented linear models for YIR and YRR. Average annual percent change (AAPC) was estimated as the weighted sum of segmented model slopes. Pearson coefficients (PC) examined correlation between YIR and YRR. RStudio performed statistics. Results: 90, 296 AVM discharges were identified from 2010–2017. AVM discharges were seen at smaller, non-academic hospitals following ARUBA (p<0.0001). SR identified a significant change in YIR during 2014. Figure 2 shows a decrease in interventions for uAVMs (28.1% vs. 22.3%, p<0.0001) and no change in rAVM interventions following ARUBA (p=0.22). uAVM discharges following ARUBA had a less likelihood of intervention than those before (OR 0.857, p=0.02); however, intervention likelihood for uAVMs with associated aneurysms were unaffected by ARUBA. Since we unexpectedly observed a higher rAVM discharge incidence following ARUBA (18.6% vs 14.7%, p<0.0001), the analysis was expanded to 2003 (154, 297 discharges). Overall, YRRs have increased (AAPC +0.49%, p=0.0001) and YIRs have decreased (AAPC -1.17%, p=0.0001; figure 1A ). The segmented AAPC for YIR was -0.63% (p=0. 0.0048) before 2014 and -3.71% (p=0. 0.0596) after 2014. Segmented YRR AAPC was -0.07% (p=0.67) before 2011 and +1.24% (p=0.0006) after 2011. An 8-year latency between YIR decrease and significant YRR change was observed. In 2017, the YRR (20.6%) surpassed the YIR (19.7%) for the first time. YIRs had a strong inverse correlation with YRRs (PC=-0.82, p=0.0002; figure 1B ). Conclusion: Following ARUBA, there has been a stark decrease in interventions for uAVMs. Nationwide rAVM discharge incidence is inversely correlated with uAVM intervention rate. Less uAVM interventions may lead to a substantial increase in AVM rupture incidence. Disclosures: D. McCarthy: None. E. Luther: None. B. Gross: None. R. Starke: None.